Evaluasi Pengujian mutu biji pepaya (Carica papaya L.) yang di ekstraksi secara maserasi dengan pelarut etanol 70% - Christica Ilsanna Surbakti; Modesta Tarigan; Grace Anastasia Ginting (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Background : In papaya seed (Carica papaya L.) the bitter taste is caused by carpain alkaloid content. Carpain is an alkaloids free class of alkaloids. This carpain alkaloid can lower blood pressure, kill amoeba, bladder stones, urinary tract, and worms. But often found traditional medicine that does not produce the expected effect, generally due to not meet the quality standard or it could be due to misinformation and mistaken assumption against traditional medicine. In terms of side effects it is recognized that traditional medicine has relatively small side effects compared to modern medicine. Therefore, researchers are interested to make a quality and efficacious extract, thus the herbal products can be maintained quality, quality and efficacy that can cure various diseases. Objectives : To find out the percentage of yield of extract after maceration of papaya seed extraction, secondary metabolite identification and characterization of papaya seed by using 70% ethanol solvent. Method : The samples used in this research are Bangkok papaya fruit seeds from Jl. Student, Ex. Marindal, Kec. Patumbak, Kab. Deli Serdang, North Sumatra. Sampling is done purposively without comparing with the same sample from other regions. This research uses experimental laboratory experimental design consist of several stages including: sample collection, making simplicia, making of extract, identification of secondary metabolite compound, and quality test of papaya seed extract (Carica papaya L.) by maceration method. Results : In result of rendement have obtained extract of ethanol thick with percentage of rendement extract equal to 15,672% from 500 gram simplicia papaya seeds. In phytochemical screening test, the compounds contained in the extract of ethanol papaya seeds seeds are alkaloids, flavonoids, saponins, steroids / triterpenoids, and tannins and on the characterization test of papaya seed extract obtained water content of 1.15%, water soluble juice content of 46.35 %, ethanol soluble content of 18.61%, total ash content of 7.25% and 0.92% acid soluble ash content that meets the extract requirements set by MMI. Conclusion : It is known that the yield after the paperasi seed extraction is done, the secondary metabolite results show negative results only on the cyanogenic glycoside test, and the characterization test has met the requirements set by MMI.